Characterization to species level of Mycobacterium avium complex strains from human immunodeficiency virus-positive and -negative patients. - Kyriakopoulos, A M (1997)
Forty human clinical Mycobacterium avium-M. intracellulare complex strains isolated in Greece were characterized to the species level by PCR with three sets of primers specific for one or both species. M. avium predominated in both human immunodeficiency virus-positive and -negative patients, but the frequency of M. intracellulare isolation appeared to be higher in the latter.